The (In)visibility of Racialized Border Violence? A Ukrainian Killed in Lisbon Airport - Garraio, Júlia (2022)
On March 12, 2020, the Ukrainian citizen Ihor Homenyuk died, having been abused and tortured while in the custody of the Foreigners and Borders Office in Lisbon airport. This crime exposed what several NGOs and institutional reports had long denounced: the climate of impunity that enabled the denial of basic human rights to immigrants in closed spaces at the Portuguese border. Understanding the media as a pivotal place of both reflection and production of social meaning, this article examines the media coverage of this case and identifies the narratives that the case fuelled and the agendas by which it was co-opted. It explores how the public invisibility of violence at Portugal’s borders, Portuguese imaginaries regarding Eastern European immigrants, and current understandings of racism helped frame the case as one of police brutality rather than as a racist crime. We aim to highlight the role of the Schengen border in the reconfiguration of racialized vulnerability and the (re)production of global hierarchies.